Design Build Mini Simulator Navigator Fish Boat (Design and Build Mini Fishing Ship Navigatioan Simulator) - Jasnur Saputra; Marjoni Marjoni (Riwayat: Educational Journal of History and Humanities, 2022)
Navigation simulators have a very important role in the learning process to steer the ship's motion safely virtually based on the same shape and function as the original. However, the absence of a navigation simulator at the Aceh Marine and Fisheries Polytechnic of the Capture Fisheries Study Program (PTK) is thought to be the cause of the non-optimal learning process so that a navigation simulator is needed. This study aims to facilitate the navigational science learning process so as to make this navigation simulator a teaching and learning tool in the classroom, both in theory and practice. The method of designing and building a mini fishing boat navigation simulator is carried out in three stages, namely the literature review method, the observation method and the field work method. The results obtained are a navigation simulator with compass, radar, electronic maps, steering, weather control, ship lights and sound signals. The building space for this fishing boat navigation simulator can be used as a learning tool to sail ships and can increase interest in learning.